1982
DOI: 10.1515/cclm.1982.20.9.633
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Activity and Activation Energy of Creatine Kinase Isoenzymes

Abstract: The catalytic activity and activation energy of an enzyme are obtained by measuring the rate of the enzymic reaction at two different temperatures. With the aid of the Arrhenius equation, these two parameters can be used to calculate a value proportional to the quantity of enzyme. Using this approach to investigate the isoenzymes of creatine kinase, it was shown that the activation energy increased in the order creatine kinase MM, MB, BB. Mixtures of the isoenzymes showed an apparent mean activation energy, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…This is also in agreement with Fig. 3 and with our recently published data on the gradual changes in apparent activation energy of CK in the human blood circulation [21]. In addition, individual u values for CK isozymes [lo], CK variants [22] and some other isoenzyme systems [23,24] have already been described.…”
Section: Discussionsupporting
confidence: 92%
“…This is also in agreement with Fig. 3 and with our recently published data on the gradual changes in apparent activation energy of CK in the human blood circulation [21]. In addition, individual u values for CK isozymes [lo], CK variants [22] and some other isoenzyme systems [23,24] have already been described.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the reported E a values for the reactions of Limulus AK (54.4 kJ/mol) and rabbit CK (49.4 kJ/mol for MM-isoform and 62.8 kJ/mol for BB-isoform (Hagelauer and Faust, 1982)) were different from those of Neocaridina AKs (Table 4). Here, it is important to note that the thermodynamics of activation only provide information leading to the rate-limiting step.…”
Section: Kinetic and Thermodynamic Properties Of The Neocaridina Aksmentioning
confidence: 76%
“…The bond lengths indicate that uMtCK may follow a dissociative catalytic mechanism. This dissociative characteristic of TS2 can be also calculated using Pauling’s formula: D (n) = D (1)−0.6logn34. Here, D (1) = 1.73 Å for the P-O bond, and D (n) is defined as the average of the two P–O distance (2.56 Å) at the translation state.…”
Section: Resultsmentioning
confidence: 99%